TESTIMONIES REVEALED BY RACIST TECHNOLOGIES:: FAMILY PHOTOGRAPHS AND RE-SIGNIFICATION OF PRECARIOUSNESS ON YOUTUBE - Pereira, Pedro Augusto (2022)
This paper analyzes photographs retrieved from family “files,” presented by Samuel Gomes in a YouTube video published on the channel Guardei no Armário. It discusses the relations of racialized subjects with the technological (im)possibilities established by the photographic production system, considering them beyond the video’s initial intention of celebration and remembrance. Based on Didi-Huberman’s reflections, these images are seen as testimonies, speech acts, that reveal much about the conditions in which they were produced. This revealed that the racism imbued in the devices contributes to consolidate a pattern of what is beautiful, subsidized in whiteness. The racist technological configuration becomes an obstacle to the construction of Black people’s memory, hindering the preservation of family records such as photographs by racialized subjects, erasing the traits and singularities of those who make up most of the Brazilian people.